ARTIFICIAL INTELLIGENCE TO IMPROVE COMMUNICATION LITERACY ON HOAX COVERAGE - Marlina, Yuli; Nizarudin Wajdi, Muh Barid; Sudarmika, Dina; Sulaeman, Maryam; Siregar, Mulki; Aminuddin Aziz, Abdullah (Ninety Media Publisher, 2025)
This study explores students' perspectives on the role of social media and artificial intelligence (AI) in verifying information while also addressing the ethical implications of using AI to combat disinformation. Conducted with 70 participants using a qualitative approach, the research relied on interviews to gain a thorough understanding of students' attitudes and viewpoints. The findings reveal that most students rely on social media to verify information and hold an optimistic view of AI's capabilities. However, concerns regarding ethical risks and diverse opinions emphasize the need for greater awareness and training in utilizing technology to combat disinformation effectively. The study highlights that students actively apply various aspects of media literacy in navigating digital information. They interpret and decode messages, assess their authenticity, classify AI as a valuable tool, recognize potential ethical risks, and exhibit an overall critical awareness of online content. These insights underscore the importance of fostering media literacy and ethical understanding in the digital age to manage information responsibly.